2020
DOI: 10.1177/2325967120953337
|View full text |Cite
|
Sign up to set email alerts
|

Revision ACL Reconstruction in Adolescent Patients

Abstract: Background: High failure rates have been documented after anterior cruciate ligament reconstruction (ACLR) in pediatric patients, and revision surgery is indicated due to high activity levels of children and adolescents. Purpose: To define trends in revision ACLR in patients who underwent initial ACLR at younger than 18 years. Study Design: Case series; Level of evidence, 4. Methods: An electronic medical record was used to retrospectively identify revision ACLR procedures performed by 2 surgeons between the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 63 publications
(83 reference statements)
0
40
0
Order By: Relevance
“…16,17,103,[106][107][108] Reasons for a second ACL injury to either knee is multifactorial. Non-modifiable factors include graft type, 20,109,110 age younger than 15 to 16, 106,111 female sex, 106 and anatomic factors. [112][113][114] Modifiable factors include returning to high-risk sports 115 and biomechanical and neuromuscular factors.…”
Section: Reinjury Rate Is High In the Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,103,[106][107][108] Reasons for a second ACL injury to either knee is multifactorial. Non-modifiable factors include graft type, 20,109,110 age younger than 15 to 16, 106,111 female sex, 106 and anatomic factors. [112][113][114] Modifiable factors include returning to high-risk sports 115 and biomechanical and neuromuscular factors.…”
Section: Reinjury Rate Is High In the Youthmentioning
confidence: 99%
“…16,17 Recent studies of revision ACLR in pediatric and adolescent populations have reported lower functional outcomes, lower return to sport rates, significant risk of contralateral ACL injury, and high rates of revision graft injury 18,19 compared to primary ACLR. Revision ACLR has also been associated with more meniscal and cartilage abnormalities, [18][19][20] which increases concern for long-term knee and general health.…”
mentioning
confidence: 99%
“…A return to sports rate, peaking at a rate of 68%, has been documented in the literature, with a return to previous level of play even lower at 55%. 72,[74][75][76] This can be because of fear of re-injury, highlighting the importance of continued counseling and discussion of realistic expectations. However, Webster et al noted a higher rate of a third ACL injury in those who returned to the pre-injury sport after revision ACL reconstruction than those who did not.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Besides considering donor site morbidity and rupture rates in favoring HT graft over BPTB or vice-versa, skeletal maturity is another important factor to consider. Many surgeons have leaned towards the use of a HT graft to perform an ACLR in skeletally immature patients to avoid harvesting a patellar tendon from an open tibial tubercle apophysis and to avoid the bone plug or interference screw from crossing and potentially arresting the physis [ 51 ]. Additionally, a lack of understanding of growth remaining in patients with open physis influences surgeons to favour other grafts for ACLR, such as the HT autograft.…”
Section: Introductionmentioning
confidence: 99%
“…However, this may put these patients at a higher risk for graft rupture because the hamstring tendons used are thinner. Therefore, the BPTB autograft is popular in ACLR for adolescent patients nearing skeletal maturity and returning to high-risk activities [ 51 ]. In patients with closed physes, the findings discussed are inconsistent.…”
Section: Introductionmentioning
confidence: 99%